Media, Culture, and Child Protection in Nigeria: Deconstructing Norms and the Limits of Rights-Based Journalism - Timothy Ekeledirichukwu Onyejelem (Britain International for Academic Research (BIAR) Publisher, 2026)
This study interrogates the complex intersection of media, culture, and child protection in Nigeria, highlighting the persistent tension between culturally embedded norms and the universalist ideals underpinning rights-based journalism. Despite Nigeria’s formal commitment to safeguarding children through frameworks such as the Child Rights Act and the United Nations Convention on the Rights of the Child, widespread violations including child abuse, labour, early marriage, and stigmatization remain deeply normalized within socio-cultural contexts. Anchored in Framing Theory, the paper examines how media narratives construct, reinforce, or challenge these cultural logics by selectively emphasizing particular interpretations of child-related issues. It argues that media framing in Nigeria is not neutral but is shaped by institutional constraints, commercial pressures, and dominant cultural beliefs, which often limit the transformative potential of rights-based journalism. The study adopts a qualitative methodology based on secondary data, drawing from peer-reviewed literature, policy documents, legal instruments, and reports from organizations such as UNICEF, alongside analyses of media practices in Nigeria. Findings reveal that while the media serves as a critical platform for advocacy and agenda-setting, it simultaneously reproduces societal norms through episodic reporting, sensationalism, and the marginalization of children’s voices. Furthermore, cultural mediation significantly influences both the interpretation of child protection and the framing of such issues in media discourse, often blurring the boundaries between discipline and abuse. The paper concludes that although rights-based journalism provides a strong normative framework for ethical reporting, its practical application in Nigeria is constrained by entrenched cultural values and structural limitations. It therefore calls for more context-sensitive, child-centred, and ethically grounded media practices that can effectively challenge harmful norms and advance the protection of children’s rights.